Development of Teaching Modules Based on Gresik Local Wisdom for Science Subjects Class IV UPT SDN 68 Gresik - Fatimah, Siti; Setyawan, Agung; Ulva Rahmi, Ulva Rahmi (Citra Dharma Cindekia, 2025)
The objectives of this development research are to (1) develop a teaching module based on Gresik local wisdom for science subjects class IV UPT SDN 68 Gresik that is valid based on expert validation. (2) developing teaching modules based on Gresik local wisdom for science subjects class IV UPT SDN 68 Gresik that are effective based on posttest scores as well as observation results. (3) developing a teaching module based on Gresik local wisdom for science subjects class IV UPT SDN 68 Gresik that is interesting based on student responses. This study uses the ADDIE model. This research was conducted in class IV UPT SDN 68 Gresik. The validity of the module is obtained from the results of the validity of the material, teaching materials, and learning design. Based on the data obtained by the researcher, the results of the material validity test were 93.34% with the